Research on Design Method of Human-in-the-loop Civil Aircraft Simulation System. Issue 7 (April 2020) - Jilei, Fu; Zhanwen, Qu; Yi, Lu; Tong, Zhang; Dan, Huang; Shan, Fu; Xinai, Zhang
Abstract: In the process of aircraft development, in the conceptual design and functional design phase before semi-physical simulation verification, it is often necessary to rely on the all-digital simulation system to design aircraft components and systems and verify that all requirements are satisfied. To meet the civil aircraft design requirements under unconventional conditions and build a holistic and comprehensive functional network, this paper demonstrates a forward design process of the scene-based civil aircraft system functional requirements identification based on the human-in-the-loop simulation system. The method proposed in this research promotes the construction of a requirement-function evidence chain. It provides a theoretical basis and method suggestions for the transformation from result control to process guarantee to support the development of civil aircraft products.